Drivers of Thailand Inflation - Arwatchanakarn, Popkarn (Journal of Applied Economics and Management Strategy, 2024)
This study explores the driver of Thailand’s inflation by employing a structural vector autoregression (SVAR) model, where monthly data on global oil prices, unemployment rates, inflation rates, policy interest rates, and exchange rates from 2002M1 to 2023M6 are deployed. The empirical results suggest that Thai inflation is primarily driven by a positive global oil price shock. Additionally, the volatility of Thai inflation is mostly explained by global oil prices, with a partial contribution from the policy rate. However, following an increase in inflation, the Bank of Thailand acts as an inflation fighter by hiking the policy rate, thereby reducing exchange rate depreciation. It is implied that a conventional monetary policy of hiking the policy rate would be optimal to fight against inflation for achieving and maintaining price stability, which is the primary objective of the Bank of Thailand, as well as beneficial for reducing Thai baht depreciation.